2017
DOI: 10.1007/978-3-319-64185-0_10
|View full text |Cite
|
Sign up to set email alerts
|

CNNs Under Attack: On the Vulnerability of Deep Neural Networks Based Face Recognition to Image Morphing

Abstract: Facial recognition has become a critical constituent of common automatic border control gates. Despite many advances in recent years, face recognition systems remain susceptible to an ever evolving diversity of spoofing attacks. It has recently been shown that high-quality face morphing or splicing can be employed to deceive facial recognition systems in a border control scenario. Moreover, facial morphs can easily be produced by means of open source software and with minimal technical knowledge. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…After that, some other metrics including attack presentation classification error rate (APCER) and the bona fide presentation classification error rate (BPCER) are complemented to evaluate the biometric systems' vulnerability to morphing attacks [6]. In addition, the vulnerability of deep learning based FRS to morphing attack was investigated in [7], and it is found that morphing attacks can degrade the performance of FRS to a certain extent.…”
Section: A Vulnerability Of Frs To Face Morphing Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, some other metrics including attack presentation classification error rate (APCER) and the bona fide presentation classification error rate (BPCER) are complemented to evaluate the biometric systems' vulnerability to morphing attacks [6]. In addition, the vulnerability of deep learning based FRS to morphing attack was investigated in [7], and it is found that morphing attacks can degrade the performance of FRS to a certain extent.…”
Section: A Vulnerability Of Frs To Face Morphing Attackmentioning
confidence: 99%
“…After this idea was put forward, some concerns about the vulnerability of commercial FRS with respect to morphed face attack have been investigated [3][4][5][6][7]. It was proved that face morphing attack is posing a serious threat to the existing FRS.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in their experiment, they use Psychomorph, which creates lower quality morphings (with more ghost artifacts) than GIMP+GAP. More examples of verification attacks can be found in L. Wandzik et al [42] and U. Scherhag [43]. In the first one, they carried out the experiment using FaceNet, utilizing more than 3000 pairs with 22 morphed images between each pair, working with triplets of images (impostor-accomplice-morphing).…”
Section: Spoofing Attacksmentioning
confidence: 99%
“…The proposed approach shows Bonafide Presentation Classification Error Rate (BPCER) value of 14.38%, 41.78%, and 28.76% at 5% Attack Presentation Classification Error Rate (APCER). Wandzik et al (2017) shows the vulnerability of deep CNN based face recognition under morphing attacks. ResNet v1 shows 99.97% acceptance rate on original images; the acceptance rate drops down to 34.66% on morphed images blended with 0.5% probability of images.…”
Section: Related Workmentioning
confidence: 99%